2018
DOI: 10.1080/09168451.2018.1459176
|View full text |Cite
|
Sign up to set email alerts
|

Anti-melanogenic effects of resorcinol are mediated by suppression of cAMP signaling and activation of p38 MAPK signaling

Abstract: In this study, we investigated the inhibitory mechanisms of resorcinol in B16F10 mouse melanoma cells. We found that resorcinol reduced both the melanin content and tyrosinase activity in these cells. In addition, resorcinol suppressed the expression of melanogenic gene microphthalmia-associated transcriptional factor (MITF) and its downstream target genes tyrosinase, tyrosinase-related protein (TRP)-1, and TRP-2. In addition, we found that resorcinol reduced intracellular cAMP levels and protein kinase A (PKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Recently, our group demonstrated the anti-melanogenic mechanisms of resorcinol, which is one of the phenolic components of argan oil 36 . Similar to beauvericin, resorcinol suppressed the enzymatic activity of tyrosinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group demonstrated the anti-melanogenic mechanisms of resorcinol, which is one of the phenolic components of argan oil 36 . Similar to beauvericin, resorcinol suppressed the enzymatic activity of tyrosinase.…”
Section: Discussionmentioning
confidence: 99%
“…The real-time RT-PCR analysis was conducted using TaqMan probes (Applied Biosystems) including Tyrosinase (ID: Mm00495818_m1), MITF (ID: Mm01182484_m1), TRP-1 (ID: Mm01268471_m1), TRP-2 (ID: Mm01225584_m1), hypoxanthine-guanine phosphoribosyltransferase (HPRT) (Mm00446966_m1), 18S (Mm04277571_s1), and GAPDH (ID: Mm99999915_g1). The PCR reaction was done with parameters as follows: 50 °C for 2 min, 60 °C for 30 min, and 95 °C for 5 min, and then 45 cycles of 94 °C for 20 s and 60 °C for 1 min as described previously 36 . The PCR results were normalized to the expression level of three housekeeping genes ( GAPDH , 18S and HPRT ) using ABI sequence detector software version 2.0 (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…As an example, it has been reported that both ferulic and caffeic acid inhibited melanin production in B16 melanoma cells, but ferulic acid reduced tyrosinase activity by directly binding to the enzyme, whereas no binding was observed in the case of caffeic acid [177]. Apart from the direct inhibition of tyrosinase activity, the anti-melanogenic activity of resorcinol in B16F10 cells has been attributed to the inhibition of cAMP signaling and activation of p38 MAPK [179]. The same applies e.g., to moracin J [181], 4,5-dicaffeoylquinic acid [183], chrysin [187], casuarictin [178], and synthetic compounds [135,136,153,197], which have been reported to both inhibit intracellular tyrosinase activity and regulate melanogenesis-related protein expression.…”
Section: Human and Animal Tyrosinase Phenolic Inhibitorsmentioning
confidence: 99%
“…The melanin-producing enzyme tyrosinase contributes vitally to the rate-limiting step of the process through which melanin is produced. Therefore, pigmentation disorders are commonly treated and skin brightening achieved by inhibiting or downregulating tyrosinase activity [17,18].…”
Section: Introductionmentioning
confidence: 99%